Elicitor Application in Strawberry Results in Long-Term Increase of Plant Resilience Without Yield Loss - Mouden, Sanae; Bac-Molenaar, Johanna A.; Kappers, Iris F.; Beerling, Ellen A. M.; Leiss, Kirsten A. (Frontiers in Plant Science, 2021)
For a first step integrating elicitor applications into current IPM strategy increasing plant resilience against pests, we investigated repeated elicitor treatments in a strawberry everbearer nursery and cropping cycle under glass. During nursery methyl-jasmonate (MeJA) was applied every three weeks, testing induction of defenses with plant bioassays. Thrips damage, as well as reproduction by spider mites, whitefly and aphids were strongly reduced upon elicitor treatment. Subsequently, we applied MeJA every three weeks, or based on scouting of pests, during a whole cropping cycle. Thrips leaf bioassays and LC-MS leaf metabolomics were applied to investigate induction of defenses. Leaf damage by trips was lower for both MeJA application schemes compared to the control except the last weeks. While elicitor treatments after scouting also reduced damage its effect did not last. Thrips damage decreased from vegetative to mature plants during the cropping cycle. At the end of the nursery phase plants in the elicitor treatment were smaller. Surprisingly, growth during production was not affected by MeJA application as were fruit yield and quality. LC-MS leaf metabolomics showed a strong induction of vegetative plants decreasing during maturation of plants towards the end of cultivation. Concurrently, no increase in the JA-inducible marker PPO, was observed when measured towards the end of cultivation. Mostly flavonoid and phenolic glycosides known as plant defense compounds were induced upon MeJA application. While induced defense decreased with maturation of plants constitutive defense increased as measured in the leaf metabolome of control plants. Our data propose that young relatively small plant stages lack constitutive defense necessitating an active JA defense response. As plants mature constitutive defense metabolites seem to accumulate providing a higher level of basal resistance. The results obtained have important implications for cultivation of strawberry showing that both vertical integration of different pest management tactics as well as horizontal integration controlling several different pests concurrently, can be realized. Moreover, regular application of elicitors during the crop cycle forms a very promising pest management tool as part of a sustainable IPM strategy not only in strawberry and other long-term cultivation crops but in production greenhouses in general.